“USING ONLINE TOOLS IN EFL CLASSES.WITH THE EXAMPLE OF JEOPARDY GAME” - Mamadjanova Maftuna Uktamovna; Mamadaliyeva Yoqutxon Abduraxim qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
One of the educational tools that have been widely used in education over the past 5 years is online learning tools. These types of tools include many features and functions that help analyze student performance and identify effective learning strategies. In this article, we will discuss what online learning tools are among these tools. Let's list the benefits of using online tools and give an example of the Jeopardy online tool.